DAMAGE OF CARBON PLASTICS FROM LOW-VELOCITY IMPACT AND THEIR RELAXATION - Shevchenko, Oleh; Andriiets, Oleksandr; Rohozhyna, Nina (Problems of Friction and Wear, 2025)
The damage assessment of carbon plastics with different filler structures based on the same epoxy matrix HexPly M 21 from low-velocity impact was carried out. The purpose of the research was to determine the difference between the depths of dents and the diameters of damage of carbon plastics that had two different fillers, namely bidirectional fabric and unidirectional carbon tape. Low-velocity impact tests were carried out with the same energy of 6.7 J per 1 mm of sample thickness. Immediately after the impact, damage parameters such as the depth of the dent and the maximum size (diameter) were measured, with the latter being determined from both the front and back sides. The depth of the dent was measured immediately after impact and after 7 days to determine the degree of damage relaxation, which reached 17%. The results of the studies are presented in the form of histograms of dent depths and damage diameters on both sides of the samples. It was found that the damage diameters for carbon plastics of both performances on the back side are significantly larger than on the front side.